2021
DOI: 10.3389/fcosc.2021.752953
|View full text |Cite
|
Sign up to set email alerts
|

Planning for Human-Wildlife Coexistence: Conceptual Framework, Workshop Process, and a Model for Transdisciplinary Collaboration

Abstract: Coexistence, as a concept and as a management goal and practice, has attracted increasing attention from researchers, managers and decision-makers dedicated to understanding and improving human-wildlife interactions. Although it still lacks a universally agreed definition, coexistence has increasingly been associated with a broad spectrum of human-wildlife interactions, including positive interactions, transcending a conservation focus on endangered wildlife, and involving explicitly considerations of power, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 55 publications
(57 reference statements)
0
14
0
1
Order By: Relevance
“…First, we propose to increase the trend toward more social scientists, community commissioners, and dedicated staff in conservation organizations. Interdisciplinarity and participatory interdisciplinarity (O'Brien et al, 2013) can enable ecologists and conservation biologists to collaborate with social scientists as well as local managers and authorities to share and combine different datasets (see also Marchini et al, 2021). Second, data collection can be integrated into a process to promote common ground consolidation (Lecuyer et al, 2018a) or dialogic decisionmaking.…”
Section: Challenges and Future Researchmentioning
confidence: 99%
“…First, we propose to increase the trend toward more social scientists, community commissioners, and dedicated staff in conservation organizations. Interdisciplinarity and participatory interdisciplinarity (O'Brien et al, 2013) can enable ecologists and conservation biologists to collaborate with social scientists as well as local managers and authorities to share and combine different datasets (see also Marchini et al, 2021). Second, data collection can be integrated into a process to promote common ground consolidation (Lecuyer et al, 2018a) or dialogic decisionmaking.…”
Section: Challenges and Future Researchmentioning
confidence: 99%
“…To fully understand the conflict drivers, their impacts, and interconnectivity, holistic views involving multiple factors (e.g., ecologic, social, cultural economic factors) need to be employed [40,[51][52][53]. Adding to this, HWC does not only touch upon conservation concerns, but also social and development issues and thus calls for transdisciplinary analysis and cross-sectoral integration of planning and action (e.g., development, health, conservation, security, waste management) [11,[54][55][56].…”
Section: Introductionmentioning
confidence: 99%
“…The scientific debate around HEC/HWC and coexistence has shown that these powerful terms may have varying definitions and evoke various reactions and emotions [45,65]. Whether we define the journey from conflict to coexistence as a continuum [66] or recognize lack of clear delineation [54] or the need to introduce a new term and concept [67], the call to change the state of conflict to something more beneficial and more equitable for those living with it is generally supported in theory [56,68].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FIGURA 1Diagrama de Interações Humano-Fauna: os dois eixos, que informam o impacto da interação sobre a fauna e sobre as pessoas, de negativo (vermelho) a positivo (azul), definem as quatro classes fundamentais de interação (adaptado deMarchini et al 2021). …”
unclassified